Antiradical and cytoprotective activities of several C-geranyl-substituted flavanones from Paulownia tomentosa fruit - Zima, Ales; Hosek, Jan; Treml, Jakub; Muselík, Jan; Suchý, Pavel; Prazanová, Gabriela; Lopes, Ana; Zemlicka, Milan (Molecules (Basel, Switzerland), 2010)
Antiradical and cytoprotective activities of several flavanones isolated from Paulownia tomentosa (Thunb.) Steud. (Scrophulariaceae) have been evaluated using different in vitro and in vivo methods. The capacity of flavanones to scavenge radicals was measured in vitro by means of DPPH and ABTS assays, the inhibition of hydroxyl radicals produced in Fenton reactions, FRAP, scavenging superoxide radicals using enzymatic and nonenzymatic assays and the inhibition of peroxynitrite-induced nitration of tyrosine. The in vivo testing involved measuring the cytoprotective effect of chosen flavanones against alloxan-induced diabetes in mice. The activity of tested compounds was expressed either as a Trolox® equivalent or was compared with rutin or morine as known antioxidant compounds. The highest activity in most tests was observed for diplacone and 3´-O-methyl-5´-hydroxydiplacone, and the structure vs. the antioxidant activity relationship of geranyl or prenyl-substituted flavonoids with different substitutions at the B and C ring was discussed.
Keywords: Cytoprotection; Animals; vztahy mezi strukturou a aktivitou; experimentální diabetes mellitus; ovoce; Diabetes Mellitus, Experimental; cytoprotekce; Structure-Activity Relationship; Free Radical Scavengers; zvířata; Mice; scavengery volných radikálů; flavanony; Flavanones; Fruit; Scrophulariaceae; myši